L’efficacité d’une intervention orthopédagogique sur le transfert des apprentissages en lecture : étude de trois cas d’élèves en difficulté - Côté, Marie-France; Mercier, Julien; Laplante, Line (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
Many authors have shown that abilities related to decoding, acquired through intensive reading interventions, did not transfer to the general ability to read text. This study aimed to test the effectiveness of a remediating reading intervention based on explicit and strategic teaching regarding transfer of knowledge in Grade 2 and 3 students experiencing reading difficulties. A multiple baseline design allowed to measure participants’ (N = 3) progress during the four weeks remediating intervention. The results show how the intervention fostered learning and transfer of knowledge for the students involved in the research.